The Taxing Wages Approach to Measuring the Tax Burden on Labour - Christopher Heady (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper outlines the methodology used by the OECD in its Taxing Wages publication, compares this approach to other measures of the effective tax rate on labour and uses recent results to illustrate its use. It argues that the strength of this methodology lies in its ability to make international comparisons of tax systems, without being affected by different population structures. However, it is limited by considering a restricted number of household types and a fairly narrow income range. Thus, this methodology should be seen as a complement to other methodologies, rather than a replacement for them.
Keywords: 330